2022
DOI: 10.1108/bfj-12-2021-1334
|View full text |Cite
|
Sign up to set email alerts
|

Using the consumption values to investigate consumer purchase intentions towards natural food products

Abstract: PurposeNatural food products are becoming more popular, and their health-related benefits are widely acknowledged. The authors wanted to see the influence of different consumption values on purchase intention of natural food products. To address this gap, the current study proposes to use theory of consumption values to explain customers purchase intention towards natural food products.Design/methodology/approachThe authors used theory of consumption values (TCV), attitude and purchase intention to develop a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 75 publications
(126 reference statements)
0
15
0
1
Order By: Relevance
“…Consumers' inclusive appraisal of a product offering grounded on their evaluations of what they deliver and what they end up receiving is recognized as perceived value (Chakraborty and Dash, 2023); it provides a pragmatic basis for competitive benefit in the marketplace (Galati et al, 2023;Khoshkam et al, 2023). The core premise influencing consumption value is the perceived usefulness that a product or service provides (Williams and Soutar, 2009).…”
Section: Local Food Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers' inclusive appraisal of a product offering grounded on their evaluations of what they deliver and what they end up receiving is recognized as perceived value (Chakraborty and Dash, 2023); it provides a pragmatic basis for competitive benefit in the marketplace (Galati et al, 2023;Khoshkam et al, 2023). The core premise influencing consumption value is the perceived usefulness that a product or service provides (Williams and Soutar, 2009).…”
Section: Local Food Consumptionmentioning
confidence: 99%
“…Recent studies have found that travelers are increasingly drawn to trying to find new engrossment and interventions as a response to understanding the customs and gastronomic ethnicity of a specific area (Balıkçıo glu Dedeo glu et al, 2022). While examining travelers' local food experiences is indeed a new concept of academic research, prior studies (Chakraborty and Dash, 2023) suggest that consuming local food can impact travelers' LFC value, which may further influence their behaviors concerning the destination's food image and attitudes toward the local cuisine (Balıkçıo glu Dedeo glu et al, 2022). Therefore, as a factual representation of modern Indian culinary traditions, examining the impact of travelers' food consumption value on their subsequent behavior within the context of local Indian food remains critical and essential.…”
Section: Introductionmentioning
confidence: 99%
“…Dalam penelitian sebelumnya, manfaat epistemik digunakan untuk menjelaskan motivasi individu dalam proses pengambilan keputusan belanja online (Koay, Cheah, & Lom, 2022). Temuan dari penelitian sebelumnya menunjukkan bahwa ketika pelanggan berada dalam situasi yang kompleks atau tidak pasti (So, Kim, & Min, 2022), menurut (Chakraborty & Dash, 2022) manfaat epistemik mengarahkan mereka untuk mencari informasi lebih lanjut. Motivasi yang dirasakan pelanggan adalah setiap manfaat yang diperoleh dari pengalaman belanja online.…”
Section: Epistemic Benefitunclassified
“…Sheth et al. (1991) postulate that this framework might apply to more than 200 buying situations, from home appliances (Dilotsotlhe and Duh, 2021), food consumption (Chakraborty and Dash, 2023; Jebarajakirthy et al. , 2021), touristic products (Rousta and Jamshidi, 2020), food delivery apps (Chakraborty et al.…”
Section: Introductionmentioning
confidence: 99%